2012
DOI: 10.1364/ao.51.006631
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional shape measurement with binary dithered patterns

Abstract: The previously proposed binary defocusing technique and its variations have proven successful for highquality three-dimensional (3D) shape measurement when fringe stripes are relatively narrow, but they suffer if fringe stripes are wide. This paper proposes to utilize the binary dithering technique to conquer this challenge. Both simulation and experimental results show the phase error is always less than 0.6% even when the fringe stripes are wide and the projector is nearly focused. Disciplines Computer-Aided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 157 publications
(57 citation statements)
references
References 14 publications
0
53
0
Order By: Relevance
“…38); they can be used to represent grayscale images with binary images and, given the fast speeds at which modern projectors can display binary images, this becomes important. In regard to dithering application in the 3-D shape measurement field, 39 Wang and Zhang's work 13 extended the simple Bayer-dithering technique and eventually the error-diffusion techniques. [40][41][42][43][44] It should be noted that these techniques improve the quality of measurement when the fringe stripes are wide; improvement is not as noticeable when the fringe stripes are narrow.…”
Section: Superfast 3-d Shape Measurement Withmentioning
confidence: 99%
See 1 more Smart Citation
“…38); they can be used to represent grayscale images with binary images and, given the fast speeds at which modern projectors can display binary images, this becomes important. In regard to dithering application in the 3-D shape measurement field, 39 Wang and Zhang's work 13 extended the simple Bayer-dithering technique and eventually the error-diffusion techniques. [40][41][42][43][44] It should be noted that these techniques improve the quality of measurement when the fringe stripes are wide; improvement is not as noticeable when the fringe stripes are narrow.…”
Section: Superfast 3-d Shape Measurement Withmentioning
confidence: 99%
“…To address this challenge, we have developed methods to improve the measurement accuracy without sacrificing the measurement speed as well as methods to increase the measurement depth range without losing measurement quality. Specifically, this article will summarize the developments of the optimal pulse width modulation (OPWM) 12 and the binary dithering/halftoning techniques 13 for high-quality superfast 3-D shape measurement with the binary defocusing method. Principles of each technique will be presented, and experimental results will be shown to verify its performance.…”
Section: Introductionmentioning
confidence: 99%
“…These methods could be divided into two categories: the 1-D pulse width modulation methods, [6][7][8][9] and the 2-D area modulation methods. [10][11][12] The former strives to separate the fundamental frequency and the high frequency harmonics further away by either shifting or eliminating high frequency harmonics. Though successful, such techniques fails to substantially improve the measurement quality when fringe stripes are very wide.…”
Section: Introductionmentioning
confidence: 99%
“…Though successful, such techniques fails to substantially improve the measurement quality when fringe stripes are very wide. 13 Taking advantages of the 2D nature of the structured patterns, area-modulation method could further improve the binary defocusing method, [10][11][12] with the dithering-based techniques being the most promising for DFP systems due to their varieties and accuracy. Furthermore, the dithering techniques could be further optimized for phase-based DFP systems.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous dithering techniques have been developed that include random dithering [8], ordered dithering [9], and error-diffusion dithering [10]. Our previous study [11] showed that these techniques could substantially enhance 3D shape measurement quality when fringe stripes are wide, but offered limited improvement when fringes are narrow. All these dithering techniques were simply applying a single matrix to convert an 8 bit grayscale image to a 1 bit binary image, ignoring the inherent image structures.…”
mentioning
confidence: 99%